2021
DOI: 10.3389/fpsyg.2021.795153
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Grit on Career Adaptability of Chinese College Students Based on the Self-Regulatory Processes

Abstract: Intelligence is innate, but grit is something everyone can develop. Grit not only enables students to stick to their goals, but also to persevere even when they fail. Career adaptability is an important concept in vocational education of college students, which is a person engaged in some work, must have a certain physical and psychological quality. Base on the self-regulation theory, this study investigated the relationship between grit and career adaptability of Chinese college student based on the self-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 82 publications
(99 reference statements)
0
9
0
2
Order By: Relevance
“…CA is self-regulation strength or capacity ( Savickas and Porfeli, 2012 ), guiding individuals to prepare and replenish resources for coping with current and imminent vocational development tasks, occupational transitions, and personal traumas ( Savickas, 1997 , 2005 ; Creed et al, 2009 ; Johnston, 2018 ), to achieve the goal of person-environment integration in the career transition ( Savickas and Porfeli, 2012 ; Pan et al, 2018 ). CA is a malleable resource ( Akkermans et al, 2020 ) and is developed through various personal experiences ( Savickas, 2013 ) and behaviors ( Guan and Frenkel, 2018 ; Chen et al, 2020 ), such as career exploration ( Cai et al, 2015 ; Guan et al, 2015 ; Li et al, 2021 ), training activities, and other activities designed to help one update existing knowledge and better adapt to changing environments [i.e., job crafting (JC); Mei et al, 2021 ]. JC is a bottom-up and repetitive work redesign process, which is perceived as an important factor in overcoming the uncertain and rapidly changing work environment and provoking CA ( Woo, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…CA is self-regulation strength or capacity ( Savickas and Porfeli, 2012 ), guiding individuals to prepare and replenish resources for coping with current and imminent vocational development tasks, occupational transitions, and personal traumas ( Savickas, 1997 , 2005 ; Creed et al, 2009 ; Johnston, 2018 ), to achieve the goal of person-environment integration in the career transition ( Savickas and Porfeli, 2012 ; Pan et al, 2018 ). CA is a malleable resource ( Akkermans et al, 2020 ) and is developed through various personal experiences ( Savickas, 2013 ) and behaviors ( Guan and Frenkel, 2018 ; Chen et al, 2020 ), such as career exploration ( Cai et al, 2015 ; Guan et al, 2015 ; Li et al, 2021 ), training activities, and other activities designed to help one update existing knowledge and better adapt to changing environments [i.e., job crafting (JC); Mei et al, 2021 ]. JC is a bottom-up and repetitive work redesign process, which is perceived as an important factor in overcoming the uncertain and rapidly changing work environment and provoking CA ( Woo, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Este estudo mostra, ainda, correlações positivas e estatisticamente significativas entre as pontuações na grit e as dimensões adaptabilidade de carreira, sendo esta correlação particulamente forte na sub-escala de preocupação, dimensão particularmente voltada para a capacidade de planeamento de atividades relacionadas com o desenvolvimento de carreira. Estes dados vêm assim reforçar a literatura que sugere que o sentido de agência, neste estudo avaliado a partir do constructo da grit, parece facilitar a capacidade de o indivíduo se adaptar positivamente à mudança de circunstâncias relacionadas com a carreira (Gregor et al, 2020;Li et al, 2021). A proximidade entre a grit e a conscienciosidade, enquanto traço de personalidade, abre possibilidades de assumirmos este constructo como relevante para a avaliação do sentido de responsabilidade, autoeficácia e perseverança dos indivíduos nos seus objetivos profissionais (Rodrigues & Gomes, 2022).…”
Section: Discussionunclassified
“…No contexto profissional, alguns autores têm encontrado associações positivas entre a grit e a adaptabilidade de carreira, constructo que se define, de um modo geral, como "a capacidade de os indivíduos se adaptarem às exigências ambientais, nomeadamente às tarefas de preparação e participação nas funções profissionais, previsíveis e imprevisíveis, provocadas por mudanças no trabalho e condições de trabalho" (Savickas, 1997, p. 254). A grit apresenta ainda uma relação positiva com o empreendedorismo (Fernández-Martin et al, 2020), processos autorregulatórios (Li et al, 2021) e estabilidade do indivíduo na atividade profissional (Rodriguez et al, 2019), podendo estas associações estar associadas a dimensões psicológicas relacionadas com a grit como perfecionismo (no sentido positivo ou proactivo), perseverança, sentido de agência e autoeficácia (Miguel et al, 2017;Rodrigues & Gomes, 2022) O constructo de grit incorpora duas dimensões: consistência dos interesses e perseverança de esforço na sua concretização. Temos assim uma dimensão mais interna ou traço (emocional e motivacional), e outra mais manifesta (comportamental), sendo ambas vistas como ingredientes essenciais ao sucesso.…”
Section: Introductionunclassified
“…Previous studies have shown the satisfactory validity and reliability of the scale among Chinese college students and professional athletes. 43 , 44 According to the recommendations of previous studies, we conducted the analysis using a single score. 8 In the current study, the Cronbach’s alpha coefficient of this scale was 0.75.…”
Section: Methodsmentioning
confidence: 99%